In Vitro Reconstitution of the End Replication Problem - Ohki, Rieko (American Society for Microbiology, 2001)
The end replication problem hypothesis proposes that the ends of linear DNA cannot be replicated completely during lagging strand DNA synthesis. Although the idea has been widely accepted for explaining telomere attrition during cell proliferation, it has never been directly demonstrated. In order to take a biochemical approach to understand how linear DNA ends are replicated, we have established a novel in vitro linear simian virus 40 DNA replication system. In this system, terminally biotin-labeled linear DNAs are conjugated to avidin-coated beads and subjected to replication reactions. Linear DNA was efficiently replicated under optimized conditions, and replication products that had replicated using the original DNA templates were specifically analyzed by purifying bead-bound replication products. By exploiting this system, we showed that while the leading strand is completely synthesized to the end, lagging strand synthesis is gradually halted in the terminal ∼500-bp region, leaving 3′ overhangs. This result is consistent with observations in telomerase-negative mammalian cells and formally demonstrates the end replication problem. This study provides a basis for studying the details of telomere replication.